Prästers absoluta tystnadsplikt och anmälningsskyldighet vid kännedom om eller misstanke att barn far illa – hur Svenska kyrkan och andra trossamfund förhåller sig till anmälningsskyldighet enligt 14 kap. 1 § socialtjänstlagen - Hansson,Hilda (2024)
Confession and absolution hold significant importance within several Christian denominations. To break the seal of confession is a violation of trust and only to be done when deemed necessary. This essay explores how the seal of confession within the Church of Sweden has been regulated by Swedish law, starting from the implementation of the current constitution of Sweden. Additionally, this essay examines the legal obligation to report concern for a child’s welfare according to 14 § 1 of the Swedish Social Services Act and its implications for religious communities. The study includes a description of how this has been conducted by three different churches: the Church of Sweden, Equmeniakyrkan (the Uniting Church in Sweden) and the Roman Catholic Church in Sweden. The purpose of this essay is to present multiple perspectives when considering the appropriateness of a legal obligation to report concern for a child’s welfare in regard to religious communities.
Keywords: förvaltningsrätt; socialrätt; rättshistoria; kyrkorätt